Analisis Markowitz dan Model Indeks Tunggal dalam Pembentukan Portofolio Optimal Saham Jakarta Islamic Index Periode 2019-2023 - Salma Febi Niti Kusumah; Liya Megawati (EKOMA : Jurnal Ekonomi, Manajemen, Akuntansi, 2024)
This research is motivated by the increasing number of sharia investors each year and the uncertainty of stock prices incorporated in the Jakarta Islamic Index in 2019-2023 so there is a needed to plan optimal portfolio to reduce the risk. Sampling in this study using purposive sampling method that meets the sample criteria as many as 15 stocks. The analysis technique used is descriptive analysis and hypothesis testing is done using the Independent Sample T-Test. The results showed that there were 3 stocks incorporated into the optimal portfolio of the Markowitz model, namely ADRO, ANTM, and BRPT, with an expected portfolio return of 0.0238 and a portfolio risk of 0.1066. And there are 4 stocks that are incorporated into the optimal portfolio of the Single Index Model, namely ADRO, BRPT, ANTM, and INCO, with an expected return of 0.0215 and a portfolio risk of 0.1035. Therefore, Markowitz portfolio is better to use than the Single Index Model portfolio because it has a greater expected return than the Single Index Model. However, statistical testing using t-test shows that the expected return and risk of the optimal portfolio of the Markowitz Model and the Single Index Model are not significantly different.